Targeting IL-6 Is a Potential Treatment for Primary Cystic Craniopharyngioma - Grob, Sydney; Mirsky, David M.; Donson, Andrew M.; Dahl, Nathan; Foreman, Nicholas K.; Hoffman, Lindsey M.; Hankinson, Todd C.; Mulcahy Levy, Jean M. (Frontiers in Oncology, 2019)
Adamantinomatous craniopharyngioma (ACP) makes up between 6 and 8% of pediatric brain tumors and is the most common pediatric tumor arising in the sellar/suprasellar region of the brain. The 10-year survival for patients diagnosed with craniopharyngioma ranges between 64 and 92%, but complicating factors such as location, common cyst formation, and potential hypothalamic infiltration cause significant morbidity in this population. There are a number of therapeutic options for children with ACP, including surgery, radiation, and cyst directed therapies such as interferon and bleomycin. Research has raised concerns regarding the efficacy and side effects associated with these conventional therapies, as well as with the difficulty in treating recurrent cystic ACP. Evidence from our group and others has shown that the cystic and solid tumor components of craniopharyngioma have high levels of IL-6R and IL-6, providing a potential target for therapy. Tocilizumab, a humanized monoclonal antibody, acts against soluble and membrane bound IL-6R, and has been widely utilized in pediatric patients. Two patients with recurrent cystic ACP were offered systemically administered tocilizumab or a combination of tocilizumab and bevacizumab on a compassionate use basis. Both patients' tumors had a significant response, with decreased cyst burden, supporting the assertion that tocilizumab with or without bevacizumab may be an option for patients suffering from cystic ACP.